2016
DOI: 10.1007/s13592-015-0423-5
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopic study on the mouthparts of Apis florea (Hymenoptera: Apidae)

Abstract: -The present study was undertaken to examine sensory structures on the mouthparts in Apis florea Fabricius (1787) from north western region (India) using scanning electron microscopy. Ultra morphological details revealed that mouthparts of the dwarf honey bees were studded with different sensory structures including sensilla chaetica (A, B and C); sensilla basiconica; sensilla trichodea C; nodulated-form sensilla trichodea C; hair membrane plate sensilla; branched processes and cuticular plate sensilla, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…SC4 and SC2 with long, nonporous cuticle wall and flexible sockets probably serve a mechanical function; moreover, they are described as odor receptors in the honey bee (Awad et al 2014). SC3 and SC1 (Table 3) are considered to have tactile and chemosensory function (Kumar & Kumar 2016). In this study, SF resemble the antennal sensilla of Dastarcus helophoroides (Ren et al 2012), Terrobittacus implicatus (Ma et al 2014), and Sitophilus granarius (Ali et al 2016).…”
Section: Philonthus Kailiensis Philonthus Lewisius Quedius Robustusmentioning
confidence: 82%
See 3 more Smart Citations
“…SC4 and SC2 with long, nonporous cuticle wall and flexible sockets probably serve a mechanical function; moreover, they are described as odor receptors in the honey bee (Awad et al 2014). SC3 and SC1 (Table 3) are considered to have tactile and chemosensory function (Kumar & Kumar 2016). In this study, SF resemble the antennal sensilla of Dastarcus helophoroides (Ren et al 2012), Terrobittacus implicatus (Ma et al 2014), and Sitophilus granarius (Ali et al 2016).…”
Section: Philonthus Kailiensis Philonthus Lewisius Quedius Robustusmentioning
confidence: 82%
“…SC4 and SC2 with long, nonporous cuticle wall and flexible sockets probably serve a mechanical function; moreover, they are described as odor receptors in the honey bee (Awad et al ). SC3 and SC1 (Table ) are considered to have tactile and chemosensory function (Kumar & Kumar ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that C. villosulum needs to lay eggs on dry bark (Dong, Dou, et al, 2020), developed SB IV and SCa may be highly helpful to the selection of oviposition sites (Xu et al, 2015). SCh, a mechanoreceptor, is widely distributed in the joints and the last segment likely because the joints are highly involved in mechanical, tactile, and chemosensory function (Kumar & Kumar, 2016; Liu et al, 2019). Previous studies have also shown that the density of sensors is closely related to sensing function (Dong, Dou, et al, 2020; Hu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%